Wieczór piosenki i humoru udział biorą: Akademicki Chór "Fred'a". (Gdynia : [s.n.], 1946)
Afisz inf. o występach.
Keywords: Gielniewski, Mieczysław -- (1892-1951).; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- życie artystyczne